Penggunaan Media Pembelajaran Berbasis Tiktok Untuk Menumbuhkan Kreativitas dan Keterampilan Merangkai Gerak Tari Kreasi Pada Peserta Didik Kelas X SMA Negeri 3 Pamekasan - Sukmana, Evy Setiawati; Huda, Nuril; Muhajir, Muhajir (Peneliti.net, 2024)
The purpose of the research is the use of TikTok-based learning media to foster creativity and skills in assembling traditional dance movements in students of class X of SMA Negeri 3 Pamekasan, Pamekasan Regency, East Java Province. The object of this research is students in class XA in a dance group consisting of 7 people in one group. The data analysis in this study is a qualitative descriptive analysis, data and information obtained from the field are described data about students' creativity in assembling creative dance movements through TikTok-based learning media in learning Cultural Arts with creative dance work materials which are carried out in four meetings. Data collection is carried out by means of observation, interviews and documentation. Based on the results of the learning research on creative dance materials, in this case, creativity in arranging creative dance movements in class X of SMA Negeri 3 Pamekasan in the dance group shows that students with good results are an indicator that they have been creative and can string dance movements into a dance work in accordance with the ideas and themes taken with musical accompaniment based on TikTok-based learning media.